THE USE OF ENGLISH SUBTITLE IN MOVIE TO IMPROVE STUDENTS’ VOCABULARY - Sembel, Natalia; Pelengkahu, Noldy; Maru, Mister Gidion (SoCul: International Journal of Research in Social Cultural Issues, 2023)
The researches want to prove that there are alternative media that can be used to help students learn English vocabulary. The aim of this study is to find out whether the use of the English subtitle in movie medium is really influential or not in upgrading students’ vocabulary knowledge. Furthermore, to find out the significant difference between students who received treatment and students who did not receive treatment in improving vocabulary of the first-grade students in SMAN 1 Kakas in academic year 2021-2022. This study is quantitative experimental study with quasi experimental approach companied by pretest-posttest control group design which includes experimental group consisted of 20 students and control group consisted of 20 students. Both groups were given pre-test and post-test. The data analysis by using t-test showed that the experimental group's average score is 68.35 and control group's average score is 56.90. It can be concluded that there is a difference in the average value of students' learning outcomes between students who received treatment and students who did not receive treatment. Therefore, the English subtitle in learning medium called movie has an effect in improving vocabulary on the first-grade students in SMAN 1 Kakas in academic year 2021-2022 and the alternative hypothesis (H1) in this study is accepted.